Five keys to powerful business relationships : how to become more productive, effective and influential - Sherman, Sallie; Sperry, Joseph; Vucelich, Steve (McGraw Hill-Ascent Audio, 2013)
What's your most valuable corporate asset? BUSINESS RELATIONSHIPS "Five Keys to Powerful Business Relationships goes beyond the usual bonhomie, grip-and-grin, back slapping ... dimension of business relationships. This book outlines a fresh, more systematic perspective to an area usually thought of as the 'soft' side of business."--The Foreword by Bradley J. Mitchell, former Chief Commercial Officer, AccuWeather Whatever business you're in, success often depends on relationships-whether the relationship is between two team members, among several divisions of a corporation, or when it spans a large network of suppliers and customers. For almost three decades Sallie Sherman, Joseph Sperry and, more recently, Steve Vucelich have been helping companies increase revenues, reduce costs, and lower risk by helping firms optimize their B2B relationships. Five Keys to Powerful Business Relationships is a game-changing guide that will help you leverage every critical relationship in your organization for greater success. The authors combine their knowledge and experience to show you how to get maximum value from virtually every relationship-both internal and external. You'll learn how to spot those relationships that are not generating their full power-and turn them into drivers of profit and growth. You'll discover new ways to eliminate barriers to performance and boost the energy of individuals, teams, groups, and your organization as a whole. And you'll find out how to improve personal and managerial development by using Five Keys to Powerful Business Relationships: Key #1: Connect first, then focus on task Key #2: Learn by walking in another's shoes Key #3: Whether people trust you is often up to you Key #4: Share information to increase your personal power Key #5: Manage yourself before you manage others The authors present proven best practices that individuals and firms can use to form more empowering relationships. They show you how to identify and remove barriers to relationships in your company, whether they are caused by culture, infrastructure, or self-awareness gaps. If you want to be more productive, effective, and influential, you have to begin thinking in terms of relationships. Globalization, quality movements, increasing numbers of M & amp;A and strategic partnerships, and the rise of social media have made relationships the new business imperative. Your company's most valuable asset may be dormant. Learn how to tap into it and extract its maximum value with Five Keys to Powerful Business Relationships